When midwives ask permission to discuss weight with pregnant women with high body weight: a qualitative study - Sofie Gyrup; Anne-Sofie Kortegaard; Sissel Due Jensen; Pernille Andreassen; Dorte Hvidtjørn (BMC, 2024)
Abstract Background In 2021, 15% of pregnant women in Denmark had a Body Mass Index (BMI) of 30 kg/m2 or more, which is associated with complications for both mothers and children. Healthcare professionals often feel insecure when discussing weight with pregnant women with high body weight, and people with high body weight are exposed to stigmatisation. To counter this, different tools have been developed to support respectful weight-related conversations, often recommending asking permission to talk about weight. This study explored the experiences of both pregnant women living with a BMI equally or above 30 kg/m2 and midwives when asking for permission to discuss weight during the initial midwife consultation. Methods We observed nine midwifery consultations and, by way of purposive sampling, interviewed six pregnant women with high body weight, while nine midwives participated in two focus group interviews. A hermeneutic-phenomenological approach by Max van Manen was applied for the analysis. Results We identified three themes in this study. "Addressing weight triggers risk and ambivalence", which explores the lived experiences of pregnant women, their personal history with their body weight and midwives' hesitancy to initiate weight-related conversations with pregnant women who have a high body weight. "Asking for permission - for whose sake?" highlights the experiences of asking permission among midwives and that pregnant women with a high body weight did not perceive the question as an opportunity to decrease weight-related conversations. "Weight conversation - a cue to feel wrong and guilty or to feel recognised as an individual?" emphasising that trust and shared decision-making are crucial factors for a relevant weight-related conversation but also that the conversation might trigger feelings such as guilt and self-doubt. Conclusion Pregnant women with high body weight had a long history with their body weight that affected all aspects of their lifeworld and influenced weight-related conversations in the midwifery consultation. Some midwives hesitated to address weight, but seeking permission eased this challenge. Despite the midwife asking for permission, some of the pregnant women felt uneasy during the conversation, leaving them with a feeling of self-doubt. Relevant conversations occurred when women engaged in decision-making and trusted the midwife.